2022
DOI: 10.1007/s00127-022-02344-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations between strengths of moral character and health: longitudinal evidence from survey and insurance claims data

Abstract: Purpose Excellent character, reflected in adherence to high standards of moral behavior, has been argued to contribute to well-being. The study goes beyond this claim and provides insights into the role of strengths of moral character (SMC) for physical and mental health. Methods This study used longitudinal observational data merged with medical insurance claims data collected from 1209 working adults of a large services organization in the US. Self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 76 publications
4
3
0
Order By: Relevance
“…In a recent longitudinal study, an orientation to promote good (consistent thoughts and taking actions that contribute to the good of oneself and others) was positively associated with multiple measures of well-being—including the subsequent life satisfaction and happiness, self-assessed mental health and physical health, social connectedness, and purpose, and meaning in life, as well as a lower risk of anxiety, loneliness, and depression [ 94 ]. These results are supported by separate longitudinal and multinational cross-sectional studies linking character strengths with health and overall quality of life [ 95 , 96 ].…”
Section: Consideration Of Human Virtues Character Strengths and Socia...supporting
confidence: 52%
“…In a recent longitudinal study, an orientation to promote good (consistent thoughts and taking actions that contribute to the good of oneself and others) was positively associated with multiple measures of well-being—including the subsequent life satisfaction and happiness, self-assessed mental health and physical health, social connectedness, and purpose, and meaning in life, as well as a lower risk of anxiety, loneliness, and depression [ 94 ]. These results are supported by separate longitudinal and multinational cross-sectional studies linking character strengths with health and overall quality of life [ 95 , 96 ].…”
Section: Consideration Of Human Virtues Character Strengths and Socia...supporting
confidence: 52%
“…Our results also indicate the protective role of orientation to promote good against anxiety, consistent with prior evidence that suggested a prospective association with self-assessed anxiety and depression and diagnosed depression but not with diagnosed anxiety at a 1-year follow-up in an American sample (Weziak-Bialowolska, Bialowolski, VanderWeele, et al, 2021;Weziak-Bialowolska, Lee, et al, 2023). However, in this prior work, only two waves of longitudinal data were used, and it is possible that concerns about reverse causality were more adequately addressed with the three waves of data used in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Although we recognize that multi-item measures are typically recommended for character and personality assessments, a single item was used because the surveys in each study were extensive and time-consuming for participants to complete. Nevertheless, a similar approach was applied in prior studies and has proved to be useful in providing evidence on the role of an orientation to promote good in the Western context (Weziak-Bialowolska, Bialowolski, VanderWeele, et al, 2021 ;Weziak-Bialowolska, Lee, et al, 2023).…”
Section: Limitationsmentioning
confidence: 99%
“…The measure has good psychometric properties, including evidence of construct validity, convergent and discriminant validity, and test-retest reliability, as well as satisfactory internal consistency for domain-specific and overall scores [5]. The utility of the overall measure and separate sub-scales has also been demonstrated in several recent studies of well-being [14,16,26].…”
Section: Outcome Variablesmentioning
confidence: 89%
“…The role of character strengths seems especially relevant for other domains of well-being. In particular, recent research found that it predicts future emotional health, physical health, social connectedness, and meaning and purpose [14][15][16][17]. What remains uncertain is whether valuing character strengths serves as a determinant of these other well-being domains.…”
Section: Introductionmentioning
confidence: 99%